Pengaruh Gerak U-Turn pada Bukaan Median terhadap Karakteristik Arus Lalu Lintas di Ruas Jalan Jenderal Ahmad Yani Kabupaten Ketapang - Putrini, Saima; Purnomo, Julyan; Larasati, Chindy (Teknik Sipil, Politeknik Negeri Ketapangg, 2024)
Jalan Jenderal Ahmad Yani, Ketapang Regency is an arterial road with environmental types, namely commercial and existing side barriers that have an impact on traffic performance due to activities beside or on the side of the road. From each of these roads, equipped with a median along with median openings to coordinate movements U-Turn. U-Turn is one way of solving in traffic management city ​​arterial road. With the aim of knowing the characteristics and capacity of traffic as well as the level of road service on the Jalan Jenderal Ahmad Yani. This matter impact on traffic characteristics, road capacity and level of service the way to be applied in research using guidelines MKJI 1997. From the results of research and discussion obtained on Jalan Jenderal Ahmad Yani with the value of traffic flow characteristics on traffic volume traffic in the direction of Jalan. Jenderal Ahmad Yani - Jalan. Merdeka at 261.95 pcu/hour and for the direction of Jalan.Merdeka - Jalan.Jenderal Ahmad Yani of 159.45 pcu/hour. Vehicle speed on Jalan General Ahmad Yani - Jalan. Merdeka of 31.41 km/hour and Jalan Merdeka – Jalan Jenderal Ahmad Yani at 34.02 km/hour. The traffic density on Jalan Jenderal Ahmad Yani – Jalan Merdeka is 8.34 smp/km and Jalan Merdeka – Jalan Jenderal Ahmad Yani of 4.69 pcu/km with traffic capacity of 1,285.90 pcu/hour. Road service level value got B and A grades.